PROSPECTS OF RAW MATERIALS FOR THE PRODUCTION OF BIODIESEL IN BRAZIL - Rodrigues, Artur S.; Rocha, Adeline C. P.; Costa, Alexandre Sylvio Vieira da; Lopes, Izaldir A. P. (International Journal of Research -GRANTHAALAYAH, 2020)
Obtaining and offering bioenergy has been identified as promising alternatives to minimize the effects caused by the uncontrolled use of oil and its derivatives. Biofuels are examples of sources of bioenergy that seek to meet the social demand in the development and establishment of concepts in the generation of new industrial technologies. In this work, information was sought from different research sources, related to the historical context of the evolution of biodiesel production with emphasis on the perspectives of the raw materials that have been most researched today, such as macauba, microalgae, sewage sludge and residual oils. Such raw materials do not compete with food production; some have great environmental advantages, such as oil residue that stops being deposited in sewers to become an alternative fuel source. In order for these alternative resources to soy to be viable for the production of biodiesel on a large scale, it is increasingly necessary to encourage public and private sector policies to insert these biomasses into the biofuel market.